Cerebral lesion correlates of sympathetic cardiovascular activation in multiple sclerosis - Winder, Klemens; Linker, Ralf A.; Seifert, Frank; Wang, Ruihao; Lee, De Hyung; Engelhorn, Tobias; Dörfler, Arnd; Fröhlich, Katharina; Hilz, Max-Josef (Human Brain Mapping, 2019)
Cardiovascular autonomic dysfunction is common in multiple sclerosis (MS) and contributes significantly to disability. We hypothesized that cerebral MS-lesions in specific areas of the central autonomic network might account for imbalance of the sympathetic and parasympathetic cardiovascular modulation. Therefore, we used voxel-based lesion symptom mapping (VLSM) to determine associations between cardiovascular autonomic dysfunction and cerebral MS-related lesion sites. In 74 MS-patients (mean age 37.0 ± 10.5 years), we recorded electrocardiographic RR-intervals and systolic and diastolic blood pressure. Using trigonometric regressive spectral analysis, we assessed low (0.04–0.15 Hz) and high (0.15–0.5 Hz) frequency RR-interval-and blood pressure-oscillations and determined parasympathetically mediated RR-interval–high-frequency modulation, mainly sympathetically mediated RR-interval–low-frequency modulation, sympathetically mediated blood pressure-low-frequency modulation, and the ratios of sympathetic and parasympathetic RR-interval-modulation as an index of sympathetic-parasympathetic balance. Cerebral MS-lesions were analyzed on imaging scans. We performed a VLSM-analysis correlating parameters of autonomic dysfunction with cerebral MS-lesion sites. The VLSM-analysis showed associations between increased RR-interval low-frequency/high-frequency ratios and lesions most prominently in the left insular, hippocampal, and right frontal inferior opercular region, and a smaller lesion cluster in the right middle cerebellar peduncle. Increased blood pressure-low-frequency powers were associated with lesions primarily in the right posterior parietal white matter and again left insular region. Our data indicate associations between a shift of cardiovascular sympathetic-parasympathetic balance toward increased sympathetic modulation and left insular and hippocampal lesions, areas of the central autonomic network. The VLSM-analysis further distinguished between right inferior fronto-opercular lesions disinhibiting cardiac sympathetic activation and right posterior parietal lesions increasing sympathetic blood pressure modulation.
CRIS-Team Scopus Importer:2019-08-23
Keywords: autonomic dysfunction; insular lesion; multiple sclerosis; visceral arousal; voxel-based lesion symptom mapping